Application of Puzzle Learning Media for Elementary School Children in Science Learning on the Metamorphosis of Frogs - Jesicha Nais; Nurmaelinda; Tina Sholikha; Rina Almaidah; Prety Nurfadhilah (Konsultan Jurnal Ilmiah Indonesia, 2025)
Science (IPA) is a crucial subject in elementary schools, encompassing natural phenomena, thinking, and problem-solving. However, students often find science difficult, abstract, and irrelevant, primarily due to unengaging teaching methods and a lack of interactive media. Recognizing this challenge, an educational initiative in Temiyang Village, Kroya District, implemented the